(untitled) (Impetus, 2026)
Physical Literacy (PL) is positioned as a fundamental approach to promote active lifestyles, sports participation, and comprehensive development from childhood. This study is a narrative review with a propositional approach, analyzing its applicability in Colombian educational and sports contexts. Based on academic literature and national regulations, the review identifies limitations in the explicit integration of PL within school curricula and sports programs, despite existing policies on physical activity and physical education. Strategic guidelines are proposed to articulate the education, health, and sports sectors, promote the design of culturally relevant assessment tools, and strengthen pedagogical practices that integrate both physical components (strength, coordination, agility, balance, and speed) and motivational and cognitive aspects (confidence, motivation, and movement understanding). The need to adapt these strategies to Colombia’s geographic and sociocultural diversity is also highlighted. This work aims to contribute to the construction of local or national PL models with a comprehensive vision that fosters inclusion, equity, and sports development. Moving towards a public policy centered on PL requires intersectoral commitment, continuous professional development, and the strengthening of school and community environments.